Evaluating implementation of Diabetes Self-Management Education in Maryland County, Liberia: protocol for a pilot prospective cohort study. Issue 10 (17th October 2022) - Trujillo, Celina; Ferrari, Gina; Ngoga, Gedeon; McLaughlin, Amy; Davies, Joe; Tucker, Anthony; Randolph, Cyrus; Cook, Rebecca; Park, Paul H; Bukhman, Gene; Adler, Alma J; Pierre, Jacquelin
Abstract : Introduction: Achieving glycaemic targets for people living with diabetes (PLWD) is challenging, especially in settings with limited resources. Programmes need to address gaps in knowledge, skills and self-management. Diabetes Self-Management Education (DSME) is an evidence-based intervention to educate and empower PLWD to improve self-management activities. This protocol describes a pilot study assessing the feasibility, acceptability and effect on clinical outcomes of implementing DSME in clinics caring for people living with insulin-dependent diabetes in Liberia. Methods and analysis: Our protocol is a three-phased, mixed-methods, quasi-experimental prospective cohort study. Phase 1 focuses on (a) establishing a Patient Advisory Board and (b) training providers in DSME who provide care for PLWD. In phase 2, clinicians will implement DSME. In phase 3, we will train additional providers who interact with PLWD. We will assess whether this DSME programme can lead to increased provider knowledge of DSME, improvements in diabetes self-management behaviours, glycaemic control, diabetes knowledge and psychosocial well-being, and a reduction in severe adverse events. Primary outcomes of interest are implementation outcomes and change in frequency of self-management behaviours by patients. Secondary outcomes include change in haemoglobin A1c, psychosocial well-being, severe adverse events and change in provider knowledge of DSME. Ethics and dissemination: Ethical approval was obtained from the University of Liberia Institutional Review Board (IRB) and the Brigham and Women's Hospital IRB. Findings from the study will be shared with local and national clinical and programmatic stakeholders and published in an open-access, peer-reviewed journal.